Blood-feeding patterns of Culex pipiens biotype pipiens and pipiens/molestus hybrids in relation to avian community composition in urban habitats - Rody Blom; Louie Krol; Melissa Langezaal; Maarten Schrama; Krijn B. Trimbos; Daan Wassenaar; Constantianus J. M. Koenraadt (Parasites & Vectors, 2024)
Abstract Background Culex pipiens sensu stricto (s.s.) is considered the primary vector of Usutu virus and West Nile virus, and consists of two morphologically identical but behaviourally distinct biotypes (Cx. pipiens biotype pipiens and Cx. pipiens biotype molestus) and their hybrids. Both biotypes are expected to differ in their feeding behaviour, and pipiens/molestus hybrids are presumed to display intermediate feeding behaviour. However, the evidence for distinct feeding patterns is scarce, and to date no studies have related differences in feeding patterns to differences in host abundance. Methods Mosquitoes were collected using CO2-baited traps. We collected blood-engorged Cx. pipiens/torrentium specimens from 12 contrasting urban sites, namely six city parks and six residential areas. Blood engorged Cx. pipiens/torrentium mosquitoes were identified to the species and biotype/hybrid level via real-time polymerase chain reaction (PCR). We performed blood meal analysis via PCR and Sanger sequencing. Additionally, avian host communities were surveyed via vocal sounds and/or visual observation. Results We selected 64 blood-engorged Cx. pipiens/torrentium mosquitoes of which we successfully determined the host origin of 55 specimens. Of these, 38 belonged to biotype pipiens, 14 were pipiens/molestus hybrids and the identity of three specimens could not be determined. No blood-engorged biotype molestus or Cx. torrentium specimens were collected. We observed no differences in feeding patterns between biotype pipiens and pipiens/molestus hybrids across different habitats. Avian community composition differed between city parks and residential areas, whereas overall avian abundance did not differ between the two habitat types. Conclusions Our results show the following: (1) Cx. pipiens s.s. feeding patterns did not differ between city parks and residential areas, regardless of whether individuals were identified as biotype pipiens or pipiens/molestus hybrids. (2) We detected differences in host availability between city parks and residential areas. (3) We show that in both urban habitat types, biotype pipiens and pipiens/molestus hybrids fed on both mammalian and avian hosts. This underscores the potential role in arbovirus transmission of biotype pipiens and pipiens/molestus hybrids. Graphical Abstract